CITRA WANITA DALAM SYAIR BANJAR KEN TAMBUHAN (The Image of the Woman in the Banjar Syair of Ken Tambuhan in South Kalimantan) - Dede Hidayatullah; Agus Yulianto; Akhmad Haries; Ahmad Dasuki; Saefuddin Saefuddin (SAWERIGADING, 2023)
The objective of this study is to describe the image of the character daughter of Ken Tambuhan. The Queen or the empress of Kuripan Kingdom, and the maids of Princess Ken Tambuhan in Ken Tabuhan's syair, which includes her physical, psychological, and social images. The problem of this research is the way the poem depicts the physical, psychological, and social images of Ken Tambuhan, the empress of Kuripan Kingdom, and the maids of Ken Tambuhan in Ken Tambuhan syair. This research uses descriptive-qualitative methods with a feminist approach. Based on the results of the analysis, it shows that: (1) Ken Tambuhan syair manuscript is an original manuscript originating from Kalimantan; the evidence is the use of the Banjar words Kulon and Kuripan, where location is in Southeast Kalimantan; namely in Amuntai City;  (2) The image of women in the syair portrays the role of women in the domestic area that do embroidery activities as a daughter of a noble family; and (3) The portrayal of unequal status for women due to their lineage. AbstrakMasalah dalam penelitian ini adalah bagaimanakah penggambaran citra fisis, psikis, dan sosial tokoh Ken Tambuhan, permaisuri Kerajaan Kuripan, dan dayang-dayang putri Ken Tambuhan di dalam syair Ken Tambuhan. Penelitian ini menggunakan metode deskriptif-kualitatif dengan pendekatan feminisme. Berdasarkan hasil analisis dapat diketahui:  (1) Syair Ken Tambuhan merupakan naskah asli yang berasal dari Kalimantan yang salah satu indikasinya karena terdapat pemakaian kata Banjar Kulon dan Kuripan yang lokasinya berada di Tenggara Kalimantan, yaitu di Kota Amuntai; (2) Citra perempuan yang terdapat dalam syair digambarkan sebagai perempuan yang hanya berada di wilayah domestik, tetapi mengerjakan pekerjaan menyulam sebagai kegiatan putri bangsawan; dan (3) Penggambaran perempuan yang masih dipandang tidak sederajat dikarenakan perbedaan status sosial seperti rakyat jelata dan bangsawan.